Cyberspace: the warfare domain - Songip, Ahmad Rahman; Md Zain, Md Zaki; Jusoff, Kamaruzaman; Jayaraman, Prebagaran; Ng, Boon Beng (IDOSI Publications, 2013)
Cyberspace is by itself a dimension that has own unique nature with characteristics that shape and affect global security environment as well as national security. The objective of this paper is to explore the nature of cyberspace as a warfare domain and assess its implications to national security. The unique nature of cyberspace as a warfare domain has different forms of impact on effect to the conduct of warfare and national security. The increasing use of advanced information systems and proliferation indicates that such development leads to cyberspace achieving a more direct implication and decisive effect to national security.